Reingeniería de procesos en contratación de servicios bancaríos - Ávila Bazurto, Carlos (2009)
After nearly 18 months working with successful development and implementation of the project NEPTUNO XI, Asociados proposed to Manager of the Bank PMI an audit to determine courses of action which allow the organization to improve efficiency, measured primarily in efficiency and cost reduction improvement in the perceived value proposition for the various customer segments. In the week of 3 to 7 September 2007, was conducted this analysis, and identified and prioritized improvement opportunities for the bank. In 2007, the Corporate Directors of PMI Bank launched an initiative to improve recruitment processes of Goods and Services Bank. Create a design team ASSOCIADOS at the Bank to develop a recruitment platform System (SW) which allows, from one point to hire all the Bank's products and services PMI. It was an integral solution (Morpheus) that improves the execution time for procurement of goods and services and the costs involved. In addition to improving the culture of information that the customer has.